The Mechanical Sub-System Machine Maintenance Analysis Using Reliability Centered Maintenance Method at PT XYZ - Bima Sugeng Pratama; Trio Yonathan Teja Kusuma (Journal of Industrial Engineering and Halal Industries, 2026)
The automotive manufacturing industry requires high operational reliability to prevent defects caused by machine failures. This research was conducted at PT XYZ, focusing on the mechanical subsystem of Line SA. The problem identified was the high frequency of machine breakdowns, specifically in the Compacting process on the PMM-60-N2 machine. This study applies the Reliability Centered Maintenance (RCM) method, utilizing Fault Tree Analysis (FTA) to find root causes and Failure Mode and Effect Analysis (FMEA) for risk assessment. The FTA results showed that the root cause of frequent breakdowns (conveyor jams and die eject failures) is the accumulation of residual powder material. FMEA calculations indicated that the Die Eject component has the highest Risk Priority Number (RPN) of 160. Based on the Logic Tree Analysis (LTA), the recommended maintenance strategy is a Scheduled On-Condition Task, emphasizing thorough cleaning and visual inspections. Implementing this strategy is expected to minimize unexpected downtime and improve overall production efficiency.